2021
DOI: 10.3389/fimmu.2020.600635
|View full text |Cite
|
Sign up to set email alerts
|

Dual Role of Hepatic Macrophages in the Establishment of the Echinococcus multilocularis Metacestode in Mice

Abstract: Echinococcus multilocularis larvae, predominantly located in the liver, cause a tumor-like parasitic disease, alveolar echinococcosis (AE), that is characterized by increased infiltration of various immune cells, including macrophages, around the lesion that produces an “immunosuppressive” microenvironment, favoring its persistent infection. However, the role of hepatic macrophages in the host defense against E. multilocularis infection remains poorly defined. Using human liver tissues from patients with AE an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
22
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(30 citation statements)
references
References 48 publications
(70 reference statements)
2
22
0
Order By: Relevance
“…It is not unusual for macrophages to show a dual role in inflammation. A study on alveolar echinococcosis revealed a dual role for hepatic macrophages, which researchers attributed to the differentiation of macrophages into different cell phenotypes at different stages ( Wang et al, 2020 ).…”
Section: Factors Involved In the Pathogenesis Of The Nsaid-associated...mentioning
confidence: 99%
“…It is not unusual for macrophages to show a dual role in inflammation. A study on alveolar echinococcosis revealed a dual role for hepatic macrophages, which researchers attributed to the differentiation of macrophages into different cell phenotypes at different stages ( Wang et al, 2020 ).…”
Section: Factors Involved In the Pathogenesis Of The Nsaid-associated...mentioning
confidence: 99%
“…For instance, the infiltration and activation of macrophages is a key feature of endoplasmic reticulum stress-induced inflammation in liver injury, with VDR signaling regulating the inflammatory response in macrophages ( 47 ). We found that two distinct macrophage proportions, Cd163-positive, the anti-inflammatory (M2 phenotype) macrophages ( 48 ), and Ccr2-positive macrophages had distinct patterns of alteration in prenatal VDD offspring. Associations between the Ccr2-positive Kupffer cells (hepatic residential macrophage) and choline-deficient amino acid-defined diet-induced hepatic steatosis and fibrosis have been identified ( 49 , 50 ).…”
Section: Discussionmentioning
confidence: 79%
“…Parasitic infection was related to the macrophage polarization patterns [10][11][12][13]. Previous studies have found that numerous macrophages gathered around the lesion in AE patients, but the disease was still getting worse, and both M1 and M2 macrophages were signi cantly higher in close liver issue (CLT) than in distant liver tissue (DLT) from the lesion [12]. Pathogen infection modulated macrophages polarization through metabolic reprogramming by the PI3K/Akt/mTOR signaling pathway [14,15].…”
Section: Introductionmentioning
confidence: 97%
“…Macrophages coordinate proin ammatory and anti-in ammatory responses to infection and play an important role in the maintenance of cell homeostasis and repair. Parasitic infection was related to the macrophage polarization patterns [10][11][12][13]. Previous studies have found that numerous macrophages gathered around the lesion in AE patients, but the disease was still getting worse, and both M1 and M2 macrophages were signi cantly higher in close liver issue (CLT) than in distant liver tissue (DLT) from the lesion [12].…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation